The role of socioeconomic status and temperament in preschoolers' emotional competence: direct and interactive effects - Si, Xinfang, author; Barrett, Karen, advisor; Hepburn, Susan, committee member; Yuma, Paula, committee member (Colorado State University. Libraries, 2022)
This study investigated the moderation effects of child temperamental characteristics on the relationship between parental socioeconomic status and child emotional competencies. Children's emotional competencies were conceptualized as emotional understanding, which was measured through puppet assessments (Denham, 1986; Cole et al., 2009). A total of 167 preschoolers (M = 47.24 months; SD = 8.38) and their parents joined the study. Hierarchical multiple regression was used to examine the direct and indirect effects of parental socioeconomic status and child temperament, as well as two key individual factors (age and gender), on children's emotional understanding. The results indicated that the interaction between SES and negative affectivity significantly predicted children's fear situation understanding. Age was a significant predictor of all emotional understandings except anger and shame situation understanding. But gender significantly predicted anger regulation understanding. Implications of these results for future studies on child emotional understanding were discussed.